1993
DOI: 10.1021/bp00019a007
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Biodegradation of Toluene and p‐Xylene in a Novel Bioreactor: Experimental Results and Mathematical Analysis

Abstract: Simultaneous biodegradation of toluene and p‐xylene was performed in a novel bioreactor, and the performance was analyzed on the basis of both experimental and mathematical simulation results. The novel bioreactor employed a silicon tubing as a supplier of the aromatic solvents to be treated, and the transfer rate of toluene and p‐xylene into the culture broth was easily controlled. Batch, sequencing batch, and continuous mode of operation were carried out in the novel bioreactor to compare the performance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…In the previous biodegradation studies on other contaminants, a similar trend in biomass yield was observed (Lee et al 1993;Paslawski et al 2009). Lee et al (1993) demonstrated that the substrate can penetrate into the cell membrane and interact with microbial membrane proteins, causing the proteins to malfunction and reducing the biomass yield. The variability in biomass yield could also be attributed to uncoupled growth.…”
Section: Effect Of Initial Diesel Concentrationsupporting
confidence: 77%
“…In the previous biodegradation studies on other contaminants, a similar trend in biomass yield was observed (Lee et al 1993;Paslawski et al 2009). Lee et al (1993) demonstrated that the substrate can penetrate into the cell membrane and interact with microbial membrane proteins, causing the proteins to malfunction and reducing the biomass yield. The variability in biomass yield could also be attributed to uncoupled growth.…”
Section: Effect Of Initial Diesel Concentrationsupporting
confidence: 77%
“…When only one growth-limiting substrate is important in determining the rate of cell proliferation, Monod (1950) kinetic model has been found suitable in explaining the biodegradation of hydrocarbons (Alvarez et al, 1991;Kelly et al, 1996;Lee et al, 1993). The kinetics constants including maximum specific growth rate, m max , saturation constant, K s , and yield coefficient, Y, were evaluated for continuous operation in the ISBR.…”
Section: Biodegradation Kineticsmentioning
confidence: 99%
“…Biofilters are packed columns with biologically active materials such as immobilized cells and compost or inorganic or polymeric media on which immobilized microbial mass is attached [7]. It was proven by several studies that biofilters are able to successfully degrade several compounds like benzene, toluene and p-xylene [9][10][11].…”
Section: Introductionmentioning
confidence: 99%